Additional Philistine Temples at Tell Qasile - Mazar, Amihai (The Biblical archaeologist, 1977)
Since 1971 excavations at Tell Qasile have revealed the existence of three Philistine temples built in succession on the same spot, beginning in the 12th century B.C.E. and ending three centuries later, when the settlement was abandoned. The finds, including three remarkable cult stands, make a valuable contribution to our understanding of Philistine culture.